comparative effect on oral and parenteral iodine supplementaion in healthly Buffalo calves - KAUR, KHUSHDEEP; RANDHAWA, S S; CHHABRA, SUSHMA (The Indian Journal of Animal Sciences, 2011)
Comparative effect of oral and parenteral iodine supplementation was investigated in healthy buffalo calves (18) which were equally divided into 3 groups. To group 1, daily oral adlninistration of potassium iodide (KI) @ O.4ppm DM was done for 7 days whereas to group 2, single injection of iodized oil was administered subcutaneously, and the group 3 was kept as controL Significant variation in plasma inorganic iodine (PII), triiodothyronine (T3)’ thyroxine (T4) and total plasma cholesterol were observed for up to 55 days in group 2. Significant increase in urinary iodine (UI), T4 and decline in T3 were noticed only up to 10th day of initiation of the oral administration of Kl. The studies suggested that single parenteral administration of iodine is more effective than daily oral iodine administration Â